Characterization of adhesive interactions between human endothelial cells and megakaryocytes - Avraham, H; Cowley, S; Chi, S; Jiang, S; Groopman, J (American Society for Clinical Investigation, 1993)
Cell-cell adhesion is essential for many immunological functions and is believed to be important in the regulation of hematopoiesis. Adhesive interactions between human endothelial cells and megakaryocytes were characterized in vitro using the CMK megakaryocytic cell line as well as marrow megakaryocytes. Although there was no adhesion between unactivated human umbilical vein endothelial cells (HUVEC) and megakaryocytes, treatment of HUVEC with inflammatory cytokines such as IL-1 beta, tumor necrosis factor alpha, INF-gamma, or the phorbol ester phorbol myristate acetate (PMA) resulted in a time- and dose-dependent increase in adhesion. Stimulation of marrow megakaryocytes or CMK cells with the cytokines IL-1 beta, GM-CSF, IL-6, IL-3, or PMA augmented their adhesion to endothelium. Monoclonal antibodies against the LFA-1 subunit of the leukocyte adherence complex CD18 inhibited the binding of marrow megakaryocytes or CMK cells to HUVEC. Adhesion blocking experiments also demonstrated that the VLA-4/VCAM-1 pathway was important for megakaryocyte attachment to HUVEC. Adhesion promoted maturation of megakaryocytic cells as measured by increased expression of glycoproteins GpIb and GpIIb/IIIa and by increased DNA content. These observations suggest that alterations in megakaryocyte adhesion may occur during inflammatory conditions, mediated by certain cytokines, resulting in augmented megakaryocyte maturation.